Application of nano TiO2 modified hollow fiber membranes in algal membrane bioreactors for high-density algae cultivation and wastewater polishing. (October 2015) - Hu, Weiming; Yin, Jun; Deng, Baolin; Hu, Zhiqiang
Highlights: Polyvinylidene fluoride (PVDF) membranes containing nano-TiO2 were fabricated. PVDF/TiO2 membranes had a better antifouling property than PVDF membranes. Mineral precipitation due to photosynthesis caused irreversible membrane resistance. Algae production rate was 6.5 ± 0.1 g/m 2 /d in lab-scale algal MBRs (A-MBRs). The A-MBRs removed 78% of phosphorus and 34% of nitrogen at the SRT of 25 d. Abstract: Polyvinylidene fluoride (PVDF) hollow fiber membranes with nano-TiO2 (5% of PVDF by mass, average size = 25 nm) additives were fabricated and applied for high-density algae ( Chlorella vulgaris ) cultivation. At the average light intensity of 121 μmol/m 2 /s, the algal membrane bioreactors (A-MBR) operated at a hydraulic retention time of 0.5 d and an average solids retention time of 25 d had an average algae biomass concentration of 2350 ± 74 mg/L (in COD units) and algal biomass production rate of 6.5 ± 0.1 g/m 2 /d. The A-MBRs removed an average of 78% of phosphorus from the wastewater at the initial total phosphorus concentrations ranging from 3.5 to 8.6 mg/L. The nano TiO2 -embedded membranes had improved surface hydrophilicity with its total resistance about 50% lower than that of the control. This study demonstrated that PVDF/TiO2 nanocomposite membranes had a better antifouling property for high-density algae cultivation and wastewater polishing.